Multilevel block in the atrioventricular node during atrial tachycardia and flutter alternating with Wenckebach phenomenon. Issue 4 (October 1979) - Slama, R; Leclercq, J F; Rosengarten, M; Coumel, P; Bouvrain, Y
Abstract : The electrocardiograms of 100 patients with rapid and regular PP intervals during atrial arrhythmias (because of atrial tachycardia or flutter, or pacing) were examined for periods of irregular atrioventricular conduction. This irregular conduction corresponds to an alternating Wenckebach phenomenon, of a type that can be determined from simple rules. The different types of conduction encountered in different patients and the changes seen in the same patient suggest that the atrioventricular node functions physiologically with 3 levels of sequential block. The different prevalence of the 2 types of alternating Wenckebach block may reflect functional differences at the level of the atrioventricular node.